Analisis Dugaan Pencemaran Nama Baik Marissa Icha Oleh Medina Zein: Kajian Linguistik Forensik - Suhermita Sihombing; Vanita Deben Simanjuntak; Yoga Baheramsyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article presents the results of an analysis of the alleged defamation case of Marissa Icha by Medina Zein. As a form of forensic linguistics study, the data in this research was analyzed descriptively-analytically using semantic and pragmatic approaches. This research found that 1) semantically, the defendants indicated that they intended to commit acts of insult and/or defamation. 2) pragmatically, the majority of these utterances fell into the form of expressive illocutions, especially to show anger or simply the personal opinion of the defendant, and thus, 3) these speeches can be said to have the potential to violate article 27 paragraph (3) of the ITE Law and articles 310 and 311 of the Criminal Code